Scar sarcoidosis: Clinical features and prognostic significance - Marcoval, Joaquim; Iriarte, Adriana; Rocamora, Gemma; Mañá, Juan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Only a few series of patients with scar sarcoidosis (SS) have been reported. Our aim was to analyse the clinical features of SS patients and their relationship to the prognosis of sarcoidosis.Methods: Patients with systemic sarcoidosis with SS diagnosed between 1980-2017 at Bellvitge University Hospital, were enrolled. Their clinical charts were reviewed to collect the following data: age, sex, ethnicity, number of lesions, location of SS, origin of the scar, association with erythema nodosum or other specific cutaneous lesions, radiological stage at diagnosis, chronic systemic sarcoidosis activity.Results: Forty two of 728 patients with systemic sarcoidosis presented SS (31 females and 11 males, mean age 47.71±13.747 years). SS was present at the onset of systemic sarcoidosis in 35/42 cases (83.33%). Twelve patients had simultaneously erythema nodosum. In 14 patients SS was the only specific cutaneous lesion of sarcoidosis. Foreign bodies were observed in 16 of 26 biopsied SS lesions (61.54%). Radiological stage at diagnosis was 0 for 2 patients, I for 22, II for 13, III for 4, and IV for 1. The activity of systemic sarcoidosis persisted for more than 5 years in 16/42 patients with SS (38.1%) vs. 186/686 patients with systemic sarcoidosis (27.11%), However the differences were not significant (p=0.154).Conclusions: SS was observed in 5.77% of our patients with systemic sarcoidosis. It is usually present at the onset of the disease and is an useful sign for suspicion of a diagnosis of sarcoidosis, but it carries no prognostic significance.